1988
DOI: 10.1016/0014-5793(88)80526-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of four types of human tyrosine hydroxylase in COS cells

Abstract: Alternative splicing from a single gene produces four kinds of human tyrosine hydroxylase (types l-4), which have structural diversity only in the N-terminal region. We attempted expression of the type l-4 enzymes in COS cells and performed kinetic analyses. All had enzymatic activities. The K, values of the four types for L-tyrosine and 6-methyl-5,6,7,8-tetrahydropteridine were similar, although their relative homospecific activities were clearly different. The type 1 enzyme displayed the highest activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 28 publications
(15 reference statements)
1
10
1
Order By: Relevance
“…Only one of the two forms was stimulated by Fe(I1) [half-maximal activation at about 20 pM Fe(II)]. Moreover, the same authors previously reported that of the four isozymes, transiently expressed in COS cells, only TH2 was activated by Fe(I1) [16]. Our results on the purified recombinant human isozymes are clearly different.…”
Section: Discussioncontrasting
confidence: 47%
“…Only one of the two forms was stimulated by Fe(I1) [half-maximal activation at about 20 pM Fe(II)]. Moreover, the same authors previously reported that of the four isozymes, transiently expressed in COS cells, only TH2 was activated by Fe(I1) [16]. Our results on the purified recombinant human isozymes are clearly different.…”
Section: Discussioncontrasting
confidence: 47%
“…Human TH yields immunoreactive bands of 62 to 68 kD [40, 41], whereas that from the rat is estimated at 60 kD [42]. Our Western blot results showed that TH protein was not detected in HUMSCs treated with NCM only.…”
Section: Resultsmentioning
confidence: 83%
“…TH, DBH, and ChAT genes could be either primary target genes of RA receptors or indirectly modulated by RA. The characterization of TH, DBH, and ChAT promoter elements (Lewis et al, 1987;Kobayashi et al, 1989;Ibanez and Persson, 1991;Bejanin et al, 1992;Shaskus et al, 1992) will now allow these possibilities to be tested by searching for RA receptor binding sites in the transcriptional control regions of the three genes.…”
Section: Discussionmentioning
confidence: 97%